A Review on Relationship Between Human Endogenous Retrovirus Groups and Human Diseases - Aramideh khouy, reza; Hosseini Tehrani, Mehrnaz; Nosrati, Hamed; Esghaei, Maryam (Archives of Medical Laboratory Sciences, 2020)
Various factors are involved in the incidence of some diseases like autoimmune, psychiatric and cancerous ones. One of these probable factors is considered as the endogenous retroviruses, for example, proviruses that have been introduced in previous generations in some organisms' genome, and make up over 8% of the human genome. Recent studies have indicated that these factors and their related products (including RNA, cytosolic DNA, and proteins) may affect and also change the host cell function and immune system. This review summarizes the detailed information about the structure, classification, and pathogenesis mechanism of human endogenous retroviruses and their relationship with the autoimmune diseases and some kinds of cancers.